Predicting residual feed intake status using rumen microbial profiles in ewe lambs1. (15th May 2019) - Ellison, Melinda J; Conant, Gavin C; Lamberson, William R; Austin, Kathleen J; van Kirk, Edward; Cunningham, Hannah C; Rule, Daniel C; Cammack, Kristi M
Abstract: Including feed efficiency as a trait for selection has gained interest in the sheep industry because it can result in reduced feed inputs or improve stocking rates, both of which translate into increased profitability for the producer. It is of interest whether the feed efficiency status of a testing population of sheep could be predicted using rumen microbial profiles associated with divergent feed efficiency status in a training population of sheep. Two populations of ewes were fed the same diet, and each group was evaluated for feed efficiency. A total of 20 animals in the testing population were selected for prediction assessment using feed efficiency, including the 6 top-ranked, the 6 bottom-ranked, and 8 middle-ranked ewes stratified over the distribution. Rumen fluid samples were collected and DNA was extracted for sequencing. Using a rumen microbial profile associated with diverging feed efficiency created from the training population, multiple discriminant analyses were performed using the DISCRIM procedure of SAS to determine the probability of correctly identifying lambs in the testing population as low, medium, or high feed efficiency using their microbial profiles. A profile of 6 rumen microbial species were used to correctly ( P < 0.001) predict all testing population ewes into their actual feed efficiency status. A regression analysis using the same microbial profile was used to predict feed efficiency values, which were strongly correlated ( r = 0.71; P < 0.001) with actual feed efficiency values. These results indicate that specific rumen microbial species may play a role in feed efficiency, and that a microbial profile could be used to rank sheep for feed efficiency.